PROSPEK BISNIS WEALTH MANAGEMENT BERBASIS SYARÎ’AH - Sri Handayani (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2008)
At the moment the growth of HNWI (High Net Worth Individual) is significantly developed. HNWI is a group of rich people having no idea in managing the properties. As a matter of course, this becomes a new prospective field on wealth management business for banking. In fact, banks dominate money market mainly in Indonesia. in accordance to this issue, this article tries to portray the following subject matters—the importance wealth management as a service product for banks customers, the factors supporting the wealth management business in Indonesia, the criteria and characteristics of HNWI, the requirements of Islamic economic principles in applying wealth management syarî’ah base, and the challenge of organizing wealth management syarî’ah -base. From public view, the existence of wealth management syarî’ah base remains significant therefore it has a huge prospect considering the decrease of loan rate. It accelerates public to invent an alternate way instead of saving. On the other hand, there is a challenge of professional profit-share, unavailability of large amount of fresh money from investor, the minimum number of people understanding the proper syarî’ah finance management, and the existence of false assumption among publics that the current syarî’ah finance system has been only symbols interchange from conventional system to Islamic ones.